ARQUITETURA E IMPLEMENTAÇÃO DE SIG MÓVEL EMBASADO EM CONCEITOS DA INTERNET DAS COISAS - Conti, Giuvane (2015)
The growth of the smartphone market, combined with the technologies used in these devices, motivates the use of this equipment in field applications because of its georeferencing potential and internet access. In cloud computing, a prominent concept is the Internet of Things (IoT) due to the exponential growth of data where are generated in day-to-day. The idea of centralization of this data, acquired from various areas, such as agriculture, urban mobility, urbanization, government, health, business, etc., are current challenges that the IoT find out to solve. It still in contrast, NoSQL databases, which have some differentiating features from relational models and they have the potential to solve some of these challenges, such as horizontal growth, high data availability and easy storage of complex structures. Another promising technology to solve some of these challenges is the RESTful, a web service that provides faster and works with fewer bytes than the communication with Simple Object Access Protocol (SOAP). In this context, this research was developed with the goal of creating a GIS Mobile application, to collect geospatial data (points, lines and polygons) and store them in an application server, in Software as a Service (SaaS) architecture, using RESTful and NoSQL. The structure follows the concept of IoT, with high potential for integration data from different areas, such as in this study. In this research were performed tests in field at the Fazenda Escola Capão-da-onça (FESCON) on 11 and 13 August 2015. A planning missions, has been pre - set to get the best results from Global Positioning System (GPS). On those dates were collected geo data on crop plots, lines and points of interest, such as erosion areas, failures in the soil and low productivity areas. The samples taken were successful and had no problems or failures, that is, the application provided facility of use and synchronization of the data with the application server. The results of the field surveys, have been exported to files in KML format and presented on thematic maps with the help of Google Earth tool. In conclusion, the project has a high potential for registration of agricultural properties and spatial geo data and, your architecture is relevant for the development of geospatial, agricultural projects in GIS Mobile area, where need to handle complex data and provide high data availability, such as Rural environmental registry (CAR, in brazil); Precision agriculture; Georeferenced control of agricultural, natural resources and urbanization data; and Business logistics applications.